The Effect of Medical-Directed Play on the Severity of Pediatric Pain During Burn Dressing Change in Children: A Clinical Randomized Trial - Atefeh Moosavi; Mahnaz Shoghi; Hamid Haghani; Leili Borimnejad (Iran University of Medical Sciences, 2019)
Background: Pain management of children with a burn is one of the most important issues in pediatrics medicine. Non-pharmacological methods of pain control can play an important role in suitable some patients. This study was aimed conducted with the aim ofto investigating investigate the effect of Medical-directed play on the severity of pediatric pain during burn dressing change in children. Methods: A randomized controlled trial was conducted on 82, 3- to 6- year-old children referring to a burn center in Tehran, Iran, for their first burn dressing change. The children were assigned into control (n=41) and intervention (n=41) groups by random allocation method. The Face, Legs, Activity, Cry, Consolability (FLACC) scale was used to measure the severity of pain before and during the dressings. The arterial blood oxygen level and pulse rate were also measured by a pulse oximeter. In the intervention group, the children were taught about the dressing steps 15 minutes before starting the procedure using a doll. The control group received routine care. The pain intensity, pulse rate, and arterial blood oxygen were compared between the groups by the Independent t-test, Paired t-test, Chi-square, and Fisher's exact exact-test using in SPSS V. 20.  Results: There was a significant difference between the groups between regarding the mean score of pain intensity during dressing between the groups (P=0.041). A significant difference was also found in the mean heart rate of the groups during dressing (P<0.001). No significant difference was seen in the arterial blood oxygen saturation between the groups. Conclusion: Medical-directed play effectively reduces pediatric procedural pain through children's cooperation during dressing changes. This cost-effective, non-invasive technique can be widely used for pain management in children with a burn.